Serving the Public Interest in Several Ways: Theory and Empirics - Robert Dur; Max van Lent (Institute of Labor Economics (IZA), 2017)
We develop a model where people differ in their altruistic preferences and can serve the public interest in two ways: by making donations to charity and by taking a public service job and exerting effort on the job. Our theory predicts that people who are more altruistic are more likely to take a public service job and, for a given job, make higher donations to charity. Comparing equally altruistic workers, those with a regular job make higher donations to charity than those with a public service job by a simple substitution argument. We subsequently test these predictions using cross-sectional data from Germany on self-reported altruism, sector of employment, and donations to charity. In addition, we use panel data from the Netherlands on volunteering and sector of employment. We find support for most of our predictions.
Keywords: D64; H11; J45; M50; 330; altruism; charitable donations; volunteering; public service motivation; public sector employment; self-selection